The Oxford handbook of health care management - Ferlie, Ewan, 1956-; Montgomery, Kathleen, 1946-; Reff Pedersen, Anne, 1970- (Oxford : Oxford University Press, 2016)
The Handbook provides an authoritative overview of current issues and debates in the field of health care management. It contains over twenty chapters from well known and eminent academic authors internationally, selected for their expertise and asked to provide a broad and critical overview of developments in their particular topic area. The development of an international perspective and body of knowledge is a key feature of the book. The Handbook secondly makes a case for bringing back a social science perspective into the study of the field of health care management. It therefore contains a number of contrasting and theoretically orientated chapters (e.g. on institutionalism; critical management studies).
Institutionalization and professionalization / Trish Reay, Elizabeth Goodrick, Bob Hinings -- Narratives of Health Policy / Graeme Currie, Graham Martin -- A New Lens on Organizational Innovations in Health Care / Stephen Shortell, Rachael Addicott -- Culture in Health Care Organizations / Russell Mannion, Huw Davies -- The Critical Health Care Management Domain / Martin Kitchener, Richard Thomas -- Interprofessional Interactions and their Impact on Professional Boundaries / Louise Fitzgerald -- Effective Team Working in Health Care / Michael A. West, Lynn Markiewicz -- Re-humanizing Health Care / Cheryl Rathert, Timothy J. Vogus, Laura McClelland -- A Discursive Approach to Organizational Health Communication / t Patient Safety and Quality / Jeffrey Braithwaite, Liam Donaldson -- Mobilizing Knowledge in Health Care / Huw Davies, Alison Powell, Sandra Nutley -- The Paradox of Health Care Performance Measurement and Management / Jenny M. Lewis -- Implementing E-Health / Bill Doolin -- Communities of Practice and Situated Learning in Health Care / Davide Nicolini, Harry Scarbrough, Julia Gracheva -- Accountability in Health Care / Haldor Byrkeflot, Karsten Vrangbaek -- Pharmaceuticals, Money, and the Health Care Organizational Field / Wendy Lipworth -- Management Consulting in Health / Ian Kirkpatrick, Chris Lonsdale, Indraneth Neogy -- Re-placing Care / Roland Bal, Lieke Oldenhof, Jeroen Postma.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 27, 2016).
Keywords: Health services administration